Immunomodulatory-associated gene transcripts to multipotency of bovine amniotic fluid mesenchymal stem cells - Baptistella, Jamila Cristina [UNESP]; da Silva, Carolina Gonzales; Báo, Sônia Nair; Panegossi, Letícia Colin [UNESP]; Cardoso, Tereza Cristina [UNESP]; de Carvalho, Roberto Gameiro [UNESP]; Martins, Carlos Frederico (FapUNIFESP (SciELO), 2024)
The adnexa fetal tissues are sources of mesenchymal stromal cells (MSCs) due to their noninvasive harvest, with all biological material discarded most of the time. MSCs are a promise regarding to their plasticity, self-renewal, differentiation potentials, immunomodulatory and anti-inflammatory properties, which have made clinical stem cell therapy a reality. The present study aimed to characterize and evaluate the immunomodulation ability of bovine mesenchymal cells collected from bovine amniotic fluid (bAFMSCs) isolated and subjected to sixth consecutive culture passages in vitro. The multilineage properties of the bAFMSCs collections confirmed the ability to undergo adipogenic, chondrogenic and osteogenic differentiation. The mesenchymal gene transcription CD106, CD73, CD29, CD90 and CD166 were detected in bAFMSCs, whereas CD34 and CD45 were not detected. Regarding cytokine mRNA expression, IL2, IL6, INFα, INFβ, INFγ, TNFα and TNFβ were downregulated, while IL10 was highly regulated in all studied passages. The present study demonstrated the immunological properties and multipotency of in vitro bAFMSCs collections, and thus, they can be tested in cattle pathological treatments or multiplication by nuclear transfer cloning.
Keywords: bovine mesenchymal stromal cells; differentiation; gene expression; immunomodulation